A Review of Factors Affecting PIT Tag Detection Using Mobile Arrays and Use of Mobile Antennas to Detect PIT‐Tagged Suckers in a Wadeable Ozark Stream. (8th April 2021) - Zentner, Douglas L.; Wolf, Skylar L.; Brewer, Shannon K.; Shoup, Daniel E.
Abstract: Advantages of PIT tags are their small size, longevity, and low cost compared to other tags. They are often used in fisheries to study movement patterns and survival or to estimate population size. However, PIT tags are limited by their short detection distance. Mobile PIT antennas may increase the utility of PIT tags in fisheries. In this study, we synthesized current detection efficiency literature for mobile PIT antennas, determined physical factors that decreased PIT tag detection probabilities for our antenna, determined factors that influenced the proportion of PIT‐tagged suckers detected by our mobile antenna, and summarized techniques used to increase detections of PIT‐tagged suckers using mobile antennas in a wadable stream. Our literature review indicated that tag size and orientation were the most important factors affecting detection probabilities. However, our manual testing suggested that the detection probability for our antenna was primarily influenced by water depth of the tag and distance from the antenna. Our sucker detection data showed that detection efficiency in our stream was most influenced by discharge, turbidity, and sample date. Tracking methods that include targeting key habitats (e.g., rootwads) and using natural features to congregate tagged fishes (e.g., riffles or pinch points) may increase detection efficiency in wadable streams. This is the first formal review of factors affecting mobile PIT antenna detection efficiency. The published literature, combined with our study results, indicates that several factors need to be considered prior to mobile PIT antenna tracking.